Oxford handbook of Karl Marx - Vidal, Matt (ed.) (New York : Oxford University Press, 2019)
The Oxford Handbook of Karl Marx provides an entry point for those new to Marxism. At the same time, its chapters, written by leading Marxist scholars, advance Marxist theory and research. Its coverage is more comprehensive than previous volumes on Marx in terms of both foundational concepts and empirical research on contemporary social problems. It also provides equal space to sociologists, economists, and political scientists, with substantial contributions from philosophers, historians and geographers. The Oxford Handbook of Karl Marx consists of seven sections. The first section, Foundations, includes chapters that demonstrate that the core elements of Marx$1 (Bs political economy of capitalism continue to be defended, elaborated and applied to empirical social science including historical materialism, class, capital, labor, value, crisis, ideology, and alienation. Additional sections include Labor, Class, and Social Divisions; Capitalist States and Spaces; Accumulation, Crisis and Class struggle in the Core Countries; Accumulation, Crisis and Class Struggle in the Peripheral and Semi-Peripheral Countries; and Alternatives to Capitalism.s
Includes bibliographical references and index.
Keywords: Marx, Karl, -- 1818-1883.; Socialism; Marxian economics